Enkele Kanttekeninge en Transendentaalkritiese Opmerkings met verwysing na die Ontstaan en Promovering van Neurolinguïstiese Programmering - Vorster, C. M.; du Plooy, J. (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2005)
During the early 1970’s two Americans, Richard Bandler en John Grinder established the Neuro-linguistic Programming model, which is a therapeutic method. The main aim of these two founding members of the NLP was to identify the therapeutic methods that were used by outstanding psychologists. With this purpose in mind, Bandler en Grinder conducted an intensive study to investigate, mainly, the psychological methods used by experts. The methods were arranged and written down according to patterns. Eventually the so-called NLP model was developed and this is used today in many fields such as in psycho-therapy with children, in education, in the business world etc. In this discussion of the historical development of the NLP the first focal point will be the origin of the fundamental patterns of the NLP model. In conclusion, while referring to the relevance of the NLP in psycho-education, certain transcendentalcritical perspectives of facets of this method will be discussed.